Improving the Size of the Propellers of the Parrot Mini-Drone and an Impact Study on its Flight Controller System - Esraa H. Kadhim; Ahmad T. Abdulsadda (International Journal of Robotics and Control Systems, 2023)
Unmanned Aerial Vehicles (UAVs) are widely used in transportation, delivery, surveillance and surveillance applications. The development of stable, resilient, and accurate flight based on turbulence and turbulence will likely become a key feature in the development of unique flight control systems. In this research, we studied the control system of a small Parrot mini drone, the Mambo drone, which was designed using the MATLAB program, while we added turbulence to the drone by changing the weight of the original plane in the design, where we increased the weight and calculated the vertical projection area of the propellers of the plane several times until we got the best space for the propellers able to carry more extra weight. We imposed an increase in the drone's weight due to bad conditions that the plane experienced during its flight, such as snow or dust falling on it. In order to make the aircraft bear these weather conditions without falling and colliding, we calculated an appropriate increase in the area of the aircraft wing, and we actually applied it in the MATLAB-R2021a Simulink program, and we got good results using simulation as well as in real-time inside the laboratory, turbulence was added in the simulation program. The new design of the propellers demonstrated the aircraft's ability to carry an additional payload of approximately one-third of the aircraft's weight, as shown in the roads chapter. In future work, we propose to use this design on larger aircraft with fixed propellers and to study the effects of other weather conditions on UAVs, such as the effect of temperature, humidity, and others.